Localization of glucocorticoid receptor mRNA in the male rat brain by in situ hybridization. - Aronsson, M (1988)
The localization and distribution of mRNA encoding the glucocorticoid receptor (GR) was investigated in tissue sections of the adult male rat brain by in situ hybridization and RNA blot analysis. GR mRNA levels were measured by quantitative autoradiography with 35S- and 32P-labeled RNA probes, respectively. Strong labeling was observed within the pyramidal nerve cells of the CA1 and CA2 areas of the hippocampal formation, in the granular cells of the dentate gyrus, in the parvocellular nerve cells of the paraventricular hypothalamic nucleus, and in the cells of the arcuate nucleus, especially the parvocellular part. Moderate labeling of a large number of nerve cells was observed within layers II, III, and VI of the neocortex and in many thalamic nuclei, especially the anterior and ventral nuclear groups as well as several midline nuclei. Within the cerebellar cortex, strong labeling was observed all over the granular layer. In the lower brainstem, strong labeling was found within the entire locus coeruleus and within the mesencephalic raphe nuclei rich in noradrenaline and 5-hydroxytryptamine cell bodies, respectively. A close correlation was found between the distribution of GR mRNA and the distribution of previously described GR immunoreactivity. These studies open the possibility of obtaining additional information on in vivo regulation of GR synthesis and how the brain may alter its sensitivity to circulating glucocorticoids.